Competing tensions: Active transport to school, school choice and policy making. (September 2020) - Sandretto, Susan; Hopkins, Debbie; Wilson, Gordon; Mandic, Sandra
Graphical abstract: Image 1 Highlights: School choice policies increase distance to school and reduce active travel rates. School leaders were aware of main barriers to active transport to/from school. Many school leaders viewed school travel as a family decision and choice. Active school travel policies have not been in the school leaders' 'field of view'. Future efforts to encourage active school travel should involve students.